Integrated Supply Chain Risk Assessment Methodology Based on Modified FMEA - KILIÇ, HÜSEYİN SELÇUK (My University, 2023)
Abstract: Supply chains have rapidly developed and become more complex to increase productivity, reduce costs and meet demand. Moreover, globalization affected complexity and uncertainty, so many risks have arisen in surviving among rivals. Today, supply chain management became more difficult for recognizing the details and controlling the process. So, recognition and assessment of the risks in advance became vital to provide the continuity of the working processes of the company and not cause big losses. This study aims to minimize the damage that may occur by providing the risk assessment. For this purpose, a risk assessment methodology in which risks are determined via literature review and expert views is proposed. Afterwards, a new technique based on Failure Mode and Effects Analysis (FMEA) is utilized. Intuitionistic Fuzzy Analytic Hierarchy Process and Weighted Product are synergistically used within FMEA. Moreover, an application in a widely known fast-moving consumer goods company is performed to validate the proposed methodology. Keywords: Risk Assessment; Supply Chain Management; Failure Mode and Effects Analysis; Intuitionistic Fuzzy Analytic Hierarchy Process; Weighted Product
Keywords: Endüstri Mühendisliği; Mühendislik ve Teknoloji; Industrial Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ENDÜSTRİYEL; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, INDUSTRIAL; Risk Assessment; Supply Chain Management; Failure Mode and Effects Analysis; Intuitionistic Fuzzy Analytic Hierarchy Process; Weighted Product